Molecular characterization of the ryanodine receptor from Adoxophyes orana and its response to lethal and sublethal doses of chlorantraniliprole - Li-na SUN; Yan-di LIU; Huai-jiang ZHANG; Wen-tao YAN; Qiang YUE; Gui-sheng QIU (Journal of Integrative Agriculture)
The insect ryanodine receptor (RyR) is a novel target of the anthranilic and phthalic insecticides, which have high activity against lepidopteran insects. Several diamide insecticides have been used to control pests in orchards in China. To enhance our understanding of the effects of diamides on RyRs, full-length cDNAs were isolated and characterized from the summer fruit tortrix moth, Adoxophyes orana, which is the most severe pest of stone and pome trees worldwide. In addition, the modulation of AoRyR mRNA expression by diamide insecticides was investigated. The AoRyR mRNA obtained had an open reading frame (ORF) of 15 402 bp nucleotides encoding 5 113 amino acids, and shared high and low identity with its orthologs in other insects and mammals of 77–92 and 45–47% identity, respectively. One alternative splice site with two exclusive exons was revealed in AoRyR (a/b). The usage of exon was more frequent in eggs and larvae than in pupae and adults. Quantitative real-time reverse transcription PCR (qRT-PCR) showed that AoRyR mRNA was expressed at all developmental stages, especially in eggs, male pupae and male adults. The expression levels of AoRyR mRNA in the whole body were up-regulated markedly after 3rd instar larvae were treated with chlorantraniliprole at LC10, LC20 and LC50 dosages. The results could provide the basis for further functional studies of AoRyR and for the development of new chemicals with selective activity against insects.